The Draft Genome Sequence of Paenibacillus polymyxa Strain CCI-25 Encompasses High Potential for Secondary Metabolite Production - Aleti, Gajender (Genome Announc, 2016)
We report here the draft genome sequence of Paenibacillus polymyxa strain CCI-25, which displays strong antifungal and antibacterial activities in vitro. The genome encompasses nonribosomal peptide synthetases predicted to encode a tridecaptin, polymyxin, fusaricidin, an iturin-like synthetase, a lantibiotic similar to paenicidin A, as well as a type 1 polyketide synthase.